Apollo 13 (CA : Universal Home Video, 1998)
A true story. Stranded 205,000 miles from Earth in a crippled spacecraft, astronauts Jim Lovell, Fred Haise, and Jack Swigert fight a desperate battle to survive. Meanwhile, at Mission Control, astronaut Ken Mattingly, flight director Gene Kranz and a heroic ground crew race against time, and the odds, to bring them home.